Main Recommendations, Proceedings and Agenda Notes - Planning Commission (Planning Commission, 1961)
Most of the farms have either been already provided with the required facilities or will be provided with them during the Third Plan period. A few farms, however, may remain without such facilities. Suitable provisions should be made for providing these facilities on all the farms during the first two years of the Third Plan by making adjustment in the States’ Plans. The seed farms on leased lands should be changed over to Government farms as quickly as possible, preferably within the first two years of the Third Plan. In one of the States the Government farms are not run by Government but Government lands are being leased to tenants for multiplication of improved seeds. This practice should be stopped and Government should run its own farms under the direct supervision and direction of the Agricultural Department.
Annual Conference on Community Development and Conference of State Ministers of Community Development and Panchayati Raj at Hyderabad